Discussion of Accounting Methods and Management Decisions: The Case of Inventory Costing and Inventory Policy - Halperin, Robert M. (Journal of Accounting Research, 1980)
Robert M. Halperin, Discussion of Accounting Methods and Management Decisions: The Case of Inventory Costing and Inventory Policy, Journal of Accounting Research, Vol. 18, Studies on Economic Consequences of Financial and Managerial Accounting: Effects on Corporate Incentives and Decisions (1980), pp. 286-291